Morphological, Molecular and Genomic Characterization of Two Inter-Subspecific Hybrids between Olive Cultivars and Olive Subspecies - Jinhua Li; Xinyue Ji; Zhaoshan Wang; Yanfei Zeng; Jianguo Zhang (Horticulturae, 2021)
Two inter-subspecific F1 hybrids have been obtained by crossing olive cultivars (‘Frantoio’ and ‘Coratina’) with pollen donors from olive subspecies (Olea europaea subsp. cuspidata) to enrich the germplasm of cultivated olive in southern China. This study aimed to investigate the characterization of morphological traits and molecular markers in the two hybrids and their parents of crosses. The morphological study showed a significant difference between genotypes according to the main discriminative parameters on qualitative and quantitative traits of leaf, fruit, and endocarp. A set of six co-dominant polymorphic simple sequence repeats (SSRs) were used for molecular identification, and SSR analysis confirmed that two progenies were the offspring of their cited parents based on the presence of parental specific SSR alleles. Three single-copy nuclear loci (SCNL) primer pairs were used for amplification of single-copy genes in the two progenies and their parents and after then PCR products were sequenced. Sequence alignment analysis on the effective data showed a total of 15 different base sites between two progenies, which were confirmed as true inter-specific hybrids between olive cultivars and subsp. cuspidata.